CITRA DAN KEPRIBADIAN MANUSIA DALAM PERSPEKTIF PSIKOLOGI ISLAM - Elawati, Susila; Warsah, Idi; Purnama Sari, Dewi (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2023)
This paper aims to examine the image and personality of human beings in the perspective of Western psychology and Islamic psychology. The writing method used is a qualitative method (qualitative research). As for the process of analyzing the data, the author uses the descriptive-analytical analysis method. This paper proves that the study of human image in the review of Western psychology and Islamic psychology has similarities. Similarly, in the humanistic school of psychology the image of the human being is seen as a good being and has unlimited potential (homo ludens). This view is consistent with the teachings of Islam as well as the Eastern people's view of man. However, in understanding human personality, Western psychology and Islamic psychology have differences. First, in the perspective of Western psychology, the study of human personality is ethically neutral, that is, it only displays the personality that appears as it is.In the perspective of Islamic psychology, the study of human personality is ethically laden, that is, it displays the personality that should be. Second, in the perspective of Western psychology, the study of personality only looks at the empirical (environmental) aspect, without looking at the mental (spiritual) aspects behind the human personality.In the perspective of Islamic psychology, the study of personality not only looks at the empirical (environmental) aspects, but also looks at the mental (spiritual) aspects that underlie the human personality. Third, in the perspective of Western psychology the study of personality is anthropocentrically oriented, which means that the human personality is influenced by human potential alone, and negates the existence of interference or will from God Almighty. Meanwhile, the study of human personality in the perspective of Islamic psychology is anthropo-religiouscentric oriented, which means that human personality is not only influenced by human potential, but also there is interference or will from God Almighty.